Elements of Business Environment. - Cherunilam, Francis (Himalaya Pub. House, 2010)
Business decisions and strategies are influenced by a number of external factors, generally referred to as Business Environment. The modern business is placed in a very complex and intricate environment. The constraints and opportunities provided by the nature of the economy and the economic system, political and legal framework, social system, geographical and ecological conditions, demographic factors etc., have profound impact on the business. The type of product to be manufactured and marketed, the marketing strategies to be employed, the way the busienss should be organised, the technolog.